FABRICATION OF SAND/ZINC OXIDE/TITANIUM DIOXIDE NANOCOMPOSITE AS PHOTOCATALYST - Idris, Nur Jannah; Bakar, Suriani Abu; Muqoyyanah, Muqoyyanah; Mohamat, Rosmanisah; Fatiatun, Fatiatun; Ahmad, Mohd Khairul (Program Studi Pendidikan Fisika, FITK, UNSIQ, 2019)
In this work, a nanocomposite photocatalyst was fabricated by growing zinc oxide (ZnO) and titanium dioxide (TiO2) on the sand as a substrate. The initial sand/ZnO was fabricated via sol-gel immersion method for 4 h at 95℃. Furthermore, the sand/ZnO/TiO2 was fabricatedusing hydrothermal method for 5 h at 150℃. Based on field emission scanning electron microscopy (FESEM) analysis, the fabricated sand/ZnO/TiO2 consists of random formation of hexagonal ZnO nanorods and two pyramidal spindle ends of TiO2 nanorods. The addition of TiO2 on top of ZnO nanorods increased the number of active sites which enables more contaminants to be absorbed thus enhanced the photocatalysis process. Moreover, based on the micro-Raman spectra, the synthesized TiO2 was in rutile phase and the ZnO peak was unobservable due to the overlapping with TiO2 peak. Based on its morphological and structural properties, the fabricated sand/ZnO/TiO2 nanocomposite was potential to be applied as photocatalyst.